Transcriptomic Signature Differences Between SARS-CoV-2 and Influenza Virus Infected Patients - Bibert, Stéphanie; Guex, Nicolas; Lourenco, Joao; Brahier, Thomas; Papadimitriou-Olivgeris, Matthaios; Damonti, Lauro; Manuel, Oriol; Liechti, Robin; Götz, Lou; Tschopp, Jonathan; Quinodoz, Mathieu; Vollenweider, Peter; et al. (Frontiers in Immunology, 2021)
The reason why most individuals with COVID-19 have relatively limited symptoms while other develop respiratory distress with life-threatening complications remains unknown. Increasing evidence suggests that COVID-19 associated adverse outcomes mainly rely on dysregulated immunity. Here, we compared transcriptomic profiles of blood cells from 103 patients with different severity levels of COVID-19 with that of 27 healthy and 22 influenza-infected individuals. Data provided a complete overview of SARS-CoV-2-induced immune signature, including a dramatic defect in IFN responses, a reduction of toxicity-related molecules in NK cells, an increased degranulation of neutrophils, a dysregulation of T cells, a dramatic increase in B cell function and immunoglobulin production, as well as an important over-expression of genes involved in metabolism and cell cycle in patients infected with SARS-CoV-2 compared to those infected with influenza viruses. These features also differed according to COVID-19 severity. Overall and specific gene expression patterns across groups can be visualized on an interactive website. Collectively, these transcriptomic host responses to SARS-CoV-2 infection are discussed in the context of current studies, thereby improving our understanding of COVID-19 pathogenesis and shaping the severity level of COVID-19.